Effect of Yeast (Saccharomyces cerevisiae) on Apparent Digestibility and Nitrogen Retention of Tomato Pomace in Sheep - Paryad, A.; Rashidi, M. (Pakistan Journal of Nutrition, 2009)
Twenty mature rams were used to determine the effects of yeast (Saccharomyces cerevisiae) on digestibility and nitrogen retention of tomato pomace. The animals were assigned randomly to one of the four different treatments (0, 2, 4 and 6 g/head/day yeast) with five rams per treatment in a completely randomized design. Each diet was fed for 14-day adaptation following a 7-day collection period whereas tomato pomace digestibility was measured by difference method using alfalfa as the basal diet. Yeast supplementation significantly (P < 0.05) increased digestibility of dry matter (DM), organic matter (OM), crude protein (CP), NDF and ADF of tomato pomace where the gross digestibility derived from the supplementation was superior in 4 gram yeast compared to the control group. In addition, sheep fed yeast had a marked increase in energy digestibility of tomato pomace at 4 gram level, however, yeast did not affect energy digestibility at 2 and 6 gram. Also, the nitrogen retention of tomato pomace was improved by Saccharomyces cerevisiae adding at 2 and 4 gram levels. The observed results were attributed to better digestibility and nitrogen retention of tomato pomace of 4 gram yeast group, possibly due to its better supply of rumen fermentation and microorganisms’ activity of digestive tract.